Qualitative Evaluation of Pedestrian Facilities using the PLOS Model - Kaur H.; Singh P.; Bivina G.R.; Nawani A. (My University, 2025)
This paper evaluates the efficiency of existing pedestrian facilities in Ludhiana, Punjab (India) using the Pedestrian Level of Service (PLOS) model. Assessment of the PLOS is essential in analysing the factors that lead to pedestrian congestion in the city. The study focuses on the major junctions and the city's core and is limited to Ludhiana considering the population projection and the proposed Land use. The paper is an exploratory study that collects and analyses data from primary and secondary sources. Primary studies included on-site observations and surveys such as user evaluation survey and pedestrian volume count, interviews, and discussions with domain experts and residents on pedestrian facilities' problems. The approach is intended to assist Urban Planners and Transportation Engineers in making informed decisions when designing road cross-sections that satisfy pedestrians' basic need and assess and prioritise the needs of existing roadways for sidewalk retrofit development. Further, this study can be used as a benchmark for pedestrianizing the other congested streets and intersections. © Published under licence by IOP Publishing Ltd.